proGenomes: a resource for consistent functional and taxonomic annotations of prokaryotic genomes - Mende, Daniel Richard; Letunić, Ivica; Huerta-Cepas, Jaime; Li, Simone S.; Forslund, Kristoffer; Sunagawa, Shinichi; Bork, Peer (Nucleic acids research, 2017)
Abstract. The availability of microbial genomes has opened many new avenues of research within microbiology. This has been driven primarily by comparative geno